If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-7x+9>-8x+14=0
We simplify the equation to the form, which is simple to understand
-7x+9>-8x+14=0
We move all terms containing x to the left and all other terms to the right.
-7x-9x=0-14
We simplify left and right side of the equation.
+2x=-14
We divide both sides of the equation by 2 to get x.
x=-7
| 2(3-2x)-x+4=0 | | -3/4(3x+7)+1/4(12x+20)= | | 7x+16-11x=28 | | 4(2x-1)-2(2x-1)=x+4 | | -3x+15=102 | | 1/2(8-4x)+1/3(9x-6)= | | 3x-11=40 | | 6x^2-8x-4=0 | | 419-20.5*10+(-5)=209 | | 8x-40=3x+50 | | in(x)=2.1 | | 3x-3=2x+13 | | 4x+9=60 | | 5x-14=8x-5 | | 419-20.5*10+(-5)= | | 5x+x=1 | | 419-20.5= | | 1/0= | | 2x+-7=-x+1 | | 2(3*x-1)(x-3)=0 | | 2x-5=8x+7-3x | | -4+3x+-1=2x+1+2x | | 4(m+6)=36 | | 5x-6(3)=7 | | 6(4f)=-24f | | 5(-1)-6y=7 | | x*x+6x-5=12 | | 2x+15=-3x+5 | | 2+4r=r-6 | | 8(2)+y=16 | | 81m^2-64=0 | | 8x-0.8=9x |